Four new species of Verbesina (Compositae: Heliantheae) of the central part of Mexico - Carrillo-Reyes, Pablo; Rzedowski, Jerzy; Calderón de Rzedowski, Graciela (Instituto de Ecología, A.C., 2010)
Based on collections gathered in the Mexican states of San Luis Potosí, Guanajuato and Querétaro, Verbesina abietifolia, V. carranzae, V. steinmannii, and V. suberosa are described as new species and illustrated.